2020
DOI: 10.3390/ma13153332
|View full text |Cite
|
Sign up to set email alerts
|

Flexibility of Biodegradable Polymer Stents with Different Strut Geometries

Abstract: Objective: Biodegradable stents (BDSs) represent a new technological development in the field of cardiovascular angioplasty; good flexibility helps stents pass through tortuous vessels during delivery and reduces the amount of damage caused to blood vessels. This study investigates the relationship between flexibility and the geometry of BDS struts. Methods: Four stent struts with different geometry (circular, triangular, hexagonal, and spline curved) and the same links were modeled to evaluate their flexibili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…Before implantation, the vascular stent must have enough flexibility to pass inside the blood vessels during delivery, maintaining the shape and the design. Once placed in the artery, the flexibility of the device must be taken into consideration since the vascular stent must have the capacity to bend to be well fitted to the blood vessel [ 26 ]. Additionally, it should resist compression from the arteries during the systolic and diastolic movements [ 23 ].…”
Section: Vascular Stentingmentioning
confidence: 99%
“…Before implantation, the vascular stent must have enough flexibility to pass inside the blood vessels during delivery, maintaining the shape and the design. Once placed in the artery, the flexibility of the device must be taken into consideration since the vascular stent must have the capacity to bend to be well fitted to the blood vessel [ 26 ]. Additionally, it should resist compression from the arteries during the systolic and diastolic movements [ 23 ].…”
Section: Vascular Stentingmentioning
confidence: 99%
“…In addition, with the increase in strut curvature, the buckling load of the component was significantly reduced. Chen et al [46] compared the deformation behavior of stents composed of curved struts and straight struts via bending experiments, and the results showed that the curved-strut-based component performed high flexibility than that of the straight-strut-based component.…”
Section: Evaluation Of Compressive Propertiesmentioning
confidence: 99%
“…There are some researchers that investigate the properties of partial differential equations defined on graphs, like in reference [7], but for observing such boundary value problems here, we find motivation in modelling mesh-like structures, like biodegradable stents. A biodegradable stent is a mesh that is used to treat the narrow or closed part of the artery to open and restore normal blood flow, which is made of a biodegradable material [8][9][10] (see Figure 1, left). However, since struts in the stent are thin, a simple structure model, called the onedimensional curved rod model, can be used (see reference [11]).…”
Section: Introductionmentioning
confidence: 99%